Fish, Ichthyomyzon bdellium, Ichthyomyzon greeleyi, Noturus flavus, Moxostoma breviceps, Lythrurus umbratilis, Notropis buccatus, Misgurnus anguillicaudatus, Morone americana, Lepomis cyanellus, Ammocrypta pellucida: distribution extensions - Robert Daniels; Douglas Carlson; Richard Morse; Bryan Weatherwax (Check List, 2006)
None